Pengaruh Kualitas Pelayanan Pegawai Terhadap Kepuasan Masyarakat Pada Kantor Pos Cabang Balige - Rini Wati; Riny Viri Insy Sinaga; Zulaili Zulaili (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to determine whether the role of UMKM and the potential of the business sector either partially or simultaneously have a significant influence on people's income in Rumah Lengo Village, STM Hulu District and what is the percentage. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the regression results of the primary data processed using SPSS 20, the multiple linear regression equation is obtained as follows: Y = 9.842 + 0.325 X1 + 0.460 X2 + e. Partially, the MSME role variable (X1) has a significant influence on people's income, as evidenced by the t count > t table (4.125 > 1.988). The variable potential of the business sector (X¬2) has a significant influence on people's income, as evidenced by the t count > t table (5.565 > 1.988). Simultaneously, the role of MSME variables (X1) and the potential of the business sector (X2) have a significant influence on people's income. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (68.444 > 3.10). The MSME role variable (X1) and the potential of the business sector (X2) are able to contribute to the purchasing decision variable by 61.7% while the remaining 38.3% is influenced by other variables not examined in this study. From the conclusions above, the authors provide suggestions to see the potential for MSMEs to have a significant influence, so the community, with the assistance of the Village Government, should further increase the zalacca chip business so that it is more developed. It is hoped that in the future there will be in-depth research conducted by other researchers regarding the variable role of MSMEs and the potential of the business sector on people's income.